Exploring The Challenges Faced By Student-Teachers In Adapting To Online Teaching - Yana Latifah; Henny Soepriyanti (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
This study aims to find out the problems faced by student-teachers in implementing online learning. A case study was chosen as the research design because the current research focused on understanding the issues faced by teaching practicum students in improving their performance when teaching using the online learning strategies. The researcher collected data through three types of data collection techniques, namely, interviews, observation, and document analysis. The results of this study show that online learning is not effective and cannot run well in learning activities in online classes. Furthermore, the results of data analysis show that students cannot develop appropriate and interesting online learning materials because they do not fully know how to develop appropriate materials due to the absence of special training for them to be able to teach and develop suitable and interesting materials during online learning activities. The findings also show that the use of online learning platforms has an effect on students' teaching performance because the lack of student participation in the implementation of online classes is more felt by students. The implication of this study is that it is crucial for educational institutions to provide comprehensive training and support in utilizing diverse online platforms for teaching purposes, ensuring that students are equipped with the necessary skills to deliver high-quality virtual instruction.